Part for cutting
Patent Information
- Application Number
- KR1020267016104
- Authority / Receiving Office
- KR · KR
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-12-08
- Filing Date
- 2024-12-03
- Publication Date
- 2026-08-11
Smart Images

Figure PCT00008_ABST
Abstract
Description
Technology Field
[0001] The present invention relates to a member for cutting, which is formed by a molded body of a resin composition. Background Technology
[0002] Conventionally, inspection mechanisms, such as semiconductor inspection jigs equipped with contact probe pins, have been used for performance testing of electronic devices, including semiconductor devices. With the recent miniaturization of semiconductors and components, inspection mechanisms utilizing these contact probe pins are required to be more precise.
[0003] Since these inspection devices require properties such as mechanical properties, heat resistance, chemical resistance, and dimensional stability, a plate-shaped super engineering plastic molded body (thermoplastic resin molded body) with numerous fine holes is used for the holding support or guide portion of the contact probe pin.
[0004] Since the thermoplastic resin constituting such a thermoplastic resin molded body is characterized by the viscosity of the resin itself, when a hole-drilling process is performed on the thermoplastic resin molded body, a string-shaped chip (so-called burr) formed by the combination of the cutting chip and the main body cutting surface is generated around the drilled opening, and this burr causes the contact probe pin to fail to insert or malfunction. Accordingly, Patent Document 1 proposes a method to suppress the generation of burrs by using a thermoplastic resin molded body incorporating a conductive filler. Prior art literature
[0005] Japanese Patent Publication No. 2005-226031 The problem to be solved
[0006] However, thermoplastic resin molded articles such as Patent Document 1 have excellent conductivity, but there is a problem that they cannot be used as insulators. In addition, in a resin molded article using carbon fibers as a conductive filler, when cutting operations such as drilling are performed, the drill bit comes into contact with the carbon fibers inside the resin molded article, causing the hole position of the workpiece to be misaligned, and thus the drilling precision is reduced.
[0007] Furthermore, as inspection mechanisms using contact probe pins require greater precision in conjunction with the recent miniaturization of semiconductors and components, there is a demand not only for suppressing burr generation during the machining of the thermoplastic resin molded bodies used therein, but also for improving machinability, such as reducing the processing time of the thermoplastic resin molded bodies. However, conventional thermoplastic resin molded bodies present a problem in that it is difficult to reduce processing time and their machinability is not yet sufficient.
[0008] The present invention is made in consideration of the above circumstances and aims to provide a cutting member that has excellent cutting performance and can suppress the generation of burrs when cutting, cutting, or drilling, etc., using a machine tool. means of solving the problem
[0009] The present invention provides a cutting member having the following configuration.
[0010] Claim 1. A machining member comprising a molded body of a resin composition containing a thermoplastic resin (A) and a reinforcing material (B), wherein the thermoplastic resin (A) is an amorphous thermoplastic resin, the reinforcing material (B) is an inorganic reinforcing material having a Mohs hardness of 5 or less, and the machinability parameter defined by the following formula (1) from the fracture toughness K1c and bending modulus of the machining member is 15m 1 / 2 to 100m 1 / 2A member for cutting, characterized by being.
[0011]
[0012] Claim 2 A machining member described in Claim 1, wherein the load bending temperature (HDT) of the machining member at a load of 1.8 MPa is 150°C or higher.
[0013] Claim 3 A cutting member described in Claim 1 or Claim 2, wherein the thermoplastic resin (A) is at least one selected from the group consisting of polyetherimide resin, polyethersulfone resin, and polyamideimide resin.
[0014] Claim 4 A cutting member described in any one of Claims 1 to 3, wherein the aspect ratio of the reinforcing material (B) is 3 to 100.
[0015] Claim 5 A member for cutting according to any one of Claims 1 to 4, wherein the reinforcing material (B) is a fibrous reinforcing material having an average fiber length of 1 μm to 300 μm.
[0016] Claim 6 A cutting member described in any one of Claims 1 to 5, wherein the reinforcing material (B) is at least one fiber selected from the group consisting of potassium titaniumate fibers, wollastonite fibers, and titania fibers.
[0017] Claim 7 A cutting member described in any one of Claims 1 to 6, wherein, in 100 mass% of the total amount of the resin composition, the content of the thermoplastic resin (A) is 20 mass% to 95 mass% and the content of the reinforcing material (B) is 5 mass% to 55 mass%.
[0018] Claim 8 The above thermoplastic resin (A) is a polyetherimide resin, and the shear rate of the resin composition is 122 sec -1 A cutting member described in any one of claims 1 to 7, having a melt viscosity of 300 Pa·s to 2600 Pa·s at a temperature of 380°C.
[0019] Claim 9 The above thermoplastic resin (A) is a polyethersulfone resin, and the shear rate of the resin composition is 122 sec -1 A cutting member described in any one of claims 1 to 7, having a melt viscosity of 230 Pa·s to 550 Pa·s at a temperature of 380°C.
[0020] Claim 10 A cutting member described in any one of Claims 1 to 9, which is a compression molded body or an extrusion molded body of the resin composition containing the thermoplastic resin (A) and the reinforcing material (B).
[0021] Claim 11 An injection-molded body of the resin composition containing the thermoplastic resin (A) and the reinforcing material (B), a member for machining as described in any one of Claims 1 to 10.
[0022] A cutting member described in any one of claims 1 to 11, which is a molded chain having a plate-like portion of claim 12.
[0023] Claim 13 A cutting member described in any one of Claims 1 to 12, used in at least one selected from the group consisting of a semiconductor inspection socket, a wafer inspection probe card, a printed circuit board inspection jig, a TAB (Tape Automated Bonding) tape inspection jig, a flexible printed circuit board inspection jig, and an inspection jig for chip components. Effects of the invention
[0024] According to the present invention, when cutting, such as milling, cutting, or drilling holes using a machine tool, a cutting member can be provided that has excellent machinability and can suppress the generation of burrs. Brief explanation of the drawing
[0025] Figure 1 is a schematic diagram showing the shape of a drill fixing jig manufactured in Example 1. Specific details for implementing the invention
[0026] Hereinafter, an example of a preferred embodiment of the present invention will be described. However, the following embodiments are merely examples. The present invention is not limited in any way to the following embodiments.
[0027] The cutting member of the present invention is composed of a molded body of a resin composition. The resin composition contains a thermoplastic resin (A) and a reinforcing material (B), and may additionally contain other additives as needed. The thermoplastic resin (A) is an amorphous thermoplastic resin. In addition, the reinforcing material (B) is an inorganic reinforcing material having a Mohs hardness of 5 or less.
[0028] In the present invention, the machinability parameter defined by the following equation (1) from the fracture toughness K1c and bending modulus of a member for machining is 15m 1 / 2 to 100m 1 / 2 am.
[0029]
[0030] The cutting member of the present invention comprises the composition of the entire present invention, in particular, the reinforcing material (B) is an inorganic reinforcing material having a Mohs hardness of 5 or less, and the cutting parameter of the cutting member is 15m 1 / 2 to 100m 1 / 2 Therefore, when performing cutting operations such as milling, cutting, or drilling using a machine tool, the cutting performance is excellent and the processing time can be shortened. In addition, the cutting member of the present invention can suppress the generation of burrs during cutting operations and can increase the precision of drilling during drilling operations.
[0031] In the present invention, the machinability parameter of the member for cutting is 15m 1 / 2 more than 100m 1 / 2 Below, preferably 15m 1 / 2 Ideally, 80m 1 / 2 Below, more preferably 15m1 / 2 Ideally, 60m 1 / 2 It is as follows. In addition, the above machinability parameter of the workpiece for machining is 15m 1 / 2 to 100m 1 / 2 , preferably 15m 1 / 2 to 80m 1 / 2 , more preferably 15m 1 / 2 to 60m 1 / 2 am.
[0032] In the present invention, the machinability parameter of the member for cutting is preferably 15m in terms of further shortening the processing time. 1 / 2 More than 22m 1 / 2 The following applies. In addition, the above machinability parameter of the member for machining is preferably 15m 1 / 2 to 22m 1 / 2 am.
[0033] In the present invention, the machinability parameter of the member for cutting is preferably 35m in terms of further suppressing the generation of burrs. 1 / 2 more than 50m 1 / 2 The following applies. In addition, the above machinability parameter of the member for machining is preferably 35m 1 / 2 up to 50m 1 / 2 am.
[0034] When the machinability parameter of the workpiece for machining is within the above range, the machinability when machining is further improved, and the generation of burrs during machining can be further suppressed.
[0035] In the present invention, the load bending temperature (HDT) of the workpiece for machining at a load of 1.8 MPa is preferably 150°C or higher. The load bending temperature (HDT) of the workpiece for machining is more preferably 165°C or higher, even more preferably 175°C or higher, and preferably 250°C or lower. In this case, the machining time can be further shortened by increasing the rotational speed of the drill bit or the feed rate during machining of the workpiece for machining. In addition, since the appearance of the cutting surface of the workpiece for machining can be improved, a cutting surface with a fine grain and good appearance can be obtained. The load bending temperature (HDT) can be adjusted by the type of thermoplastic resin (A), the amount of reinforcing material (B) mixed, the molding method, etc.
[0036] Each component of the resin composition constituting the cutting member of the present invention is described below.
[0037] <Resin Composition>
[0038] The resin composition used in the present invention contains a thermoplastic resin (A) and a reinforcing material (B), and may additionally contain other additives as needed. Each component of the resin composition used in the present invention is described below.
[0039] (Thermoplastic resin (A))
[0040] The thermoplastic resin (A) used in the present invention is an amorphous thermoplastic resin. In addition, "crystallization" means that the value of the heat of dissolution measured by a heating rate of 10°C / min after cooling from a molten state to 50°C under a nitrogen atmosphere using a differential scanning calorimeter (DSC) is greater than 30 J / g. "Amorphization" means that the value of the heat of dissolution measured by a heating rate of 10°C / min after cooling from a molten state to 50°C under a nitrogen atmosphere using a DSC is 30 J / g or less.
[0041] Examples of amorphous thermoplastic resins include polystyrene resin, polymethyl methacrylate resin, acrylonitrile-butadiene-styrene resin, polycarbonate resin, modified polyphenylene ether resin, polyetherimide resin, polyethersulfone resin, or polyamideimide resin. It is preferable that the amorphous thermoplastic resin be at least one selected from the group consisting of polyetherimide resin, polyethersulfone resin, and polyamideimide resin. In this case, the heat resistance, chemical resistance, and dimensional stability of the cutting member can be improved to a higher level. These amorphous thermoplastic resins may each be used individually or in combination of two or more types.
[0042] Among these amorphous thermoplastic resins, it is preferable that the thermoplastic resin (heat-resistant resin) has a glass transition temperature of 170°C or higher. The glass transition temperature can be measured by differential scanning calorimetry (DSC). Since the amorphous thermoplastic resin is the heat-resistant resin mentioned above, even when cutting operations such as drilling are performed on a cutting member, deformation or discoloration due to frictional heat is less likely to occur.
[0043] In the case where the thermoplastic resin (A) is a polyetherimide resin, a shear rate of 122 sec at a temperature 100°C to 170°C higher than the glass transition temperature using a capillary rheometer -1 It is preferable that the melt viscosity measured by [method] is 300 Pa·s to 2600 Pa·s. In addition, when the thermoplastic resin (A) is a polyethersulfone resin, a shear rate of 122 sec at a temperature 100°C to 170°C higher than the glass transition temperature using a capillary rheometer -1 It is preferable that the melt viscosity measured by [method] is 200 Pa·s to 550 Pa·s.
[0044] When the thermoplastic resin (A) is a polyetherimide resin, the shear rate of the resin composition constituting the machining member is 122 sec -1 and at a temperature of 380°C, it is preferable that the melt viscosity is 300 Pa·s to 2600 Pa·s, and more preferable that it is 300 Pa·s to 2000 Pa·s. In addition, when the thermoplastic resin (A) is a polyethersulfone resin, the shear rate of the resin composition constituting the cutting member is 122 sec -1 And it is preferable that the melt viscosity at a temperature of 380°C is 230 Pa·s to 550 Pa·s. When the melt viscosity of the resin composition is within the above range, the moldability of the member for cutting can be further improved.
[0045] The content of the thermoplastic resin (A) is preferably 20 mass% to 95 mass% in the total amount of 100 mass% of the resin composition, more preferably 35 mass% to 85 mass%, and even more preferably 40 mass% to 80 mass%. By keeping the content of the thermoplastic resin (A) within the above range, the machinability of the cutting member can be further improved.
[0046] (Reinforcement material (B))
[0047] The reinforcing material (B) used in the present invention is an inorganic reinforcing material having a Mohs hardness of 5 or less, and is particularly preferably a powdered inorganic reinforcing material composed of particles having a Mohs hardness of 5 or less. The Mohs hardness of the inorganic reinforcing material is preferably 2 or more and 5 or less. Furthermore, Mohs hardness is an indicator of the hardness of a material, and the material with the lower hardness is the one that scratches when minerals are rubbed against each other. In the present invention, Mohs hardness may be calculated based on Vickers hardness.
[0048] The reinforcing material (B) is a powder-type inorganic reinforcing material composed of particles, and as long as it improves the strength or stiffness of a member for machining, the shape of the particles is not particularly limited. As for the reinforcing material (B), for example, a fibrous reinforcing material (B1) which is a powder composed of fibrous particles, or a plate-type reinforcing material (B2) which is a powder composed of plate-type particles, can be used. It is preferable that the reinforcing material (B) be one or more types selected from the group consisting of fibrous reinforcing material (B1) and plate-type reinforcing material (B2). The shape of the particles of the reinforcing material (B) can be determined, for example, by observation with a scanning electron microscope (SEM).
[0049] In the present invention, fibrous particles refer to particles in which L / B and L / T are both 3 or greater, where L is the longest side of the rectangular prism having the smallest volume among the rectangular prisms circumscribed around the particle (circumscribed rectangular prism), B is the next longest side, and T is the thickness (B > T). L is the longest side, and B is the shortest side. Additionally, plate-like particles refer to particles in which L / B is less than 3 and L / T is 3 or greater.
[0050] Specific examples of the fibrous reinforcing material (B1) include inorganic fibers such as potassium titanium fiber, wollastonite fiber, aluminum borate fiber, magnesium borate fiber, zonotlite fiber, zinc oxide fiber, basic magnesium sulfate fiber, alumina fiber, silicon carbide fiber, boron fiber, or titania fiber. The potassium titanium fiber may be a potassium titanium fiber with its surface coated with a conductive material such as tin oxide or antimony oxide. The titania fiber may be a monoclinic titania fiber with its surface coated with a conductive material such as tin oxide or antimony oxide. These fibrous reinforcing materials (B1) may be used as a single type or in combination of multiple types.
[0051] The fibrous reinforcing material (B1) is preferably a particle with a Mohs hardness of 2 or higher and 5 or lower, with the intention of further improving the precision of drilling while suppressing the generation of burrs during the drilling process of a cutting-processing member, more preferably at least one of potassium titaniumate fiber and wollastonite fiber, and particularly preferably potassium titaniumate fiber.
[0052] The average fiber length of the fibrous reinforcement (B1) is preferably 1 μm to 300 μm, more preferably 1 μm to 200 μm, even more preferably 3 μm to 100 μm, and particularly preferably 5 μm to 50 μm, in order to further improve machinability when cutting or slicing a workpiece for machining or when drilling a hole with a drill bit, etc. In addition, the average fiber diameter of the fibrous reinforcement (B1) is preferably 0.01 μm to 1 μm, more preferably 0.03 μm to 0.9 μm, even more preferably 0.05 μm to 0.8 μm, and particularly preferably 0.1 μm to 0.7 μm. In addition, the average aspect ratio of the fibrous reinforcement (B1) is preferably 3 to 200, more preferably 3 to 100, even more preferably 3 to 50, and particularly preferably 3 to 40.
[0053] As potassium titaniumate fibers, conventionally known fibers can be widely used, and examples include potassium tetratitanate fibers, potassium hexatitanate fibers, potassium octatate fibers, etc. The dimensions of the potassium titaniumate fibers are not particularly limited as long as they fall within the range of dimensions of the fibrous reinforcing material (B1) described above, but the average fiber length is preferably 1 μm to 50 μm, more preferably 3 μm to 30 μm, and even more preferably 3 μm to 20 μm. The average fiber diameter of the potassium titaniumate fibers is preferably 0.01 μm to 1 μm, more preferably 0.05 μm to 0.8 μm, and even more preferably 0.1 μm to 0.7 μm. In addition, the average aspect ratio of the potassium titaniumate fibers is preferably 10 or more, more preferably 10 to 100, and even more preferably 15 to 35.
[0054] Wollastonite fibers are inorganic fibers containing calcium metasilicate. The dimensions of the wollastonite fibers are not particularly limited as long as they fall within the range of dimensions of the fibrous reinforcing material (B1) described above, but the average fiber length is preferably 5 μm to 180 μm, more preferably 7 μm to 100 μm, and even more preferably 9 μm to 40 μm. The average fiber diameter of the wollastonite fibers is preferably 0.1 μm to 15 μm, more preferably 1 μm to 10 μm, and even more preferably 2 μm to 7 μm. In addition, the average aspect ratio of the wollastonite fibers is preferably 3 or more, more preferably 3 to 30, and even more preferably 3 to 15.
[0055] The average fiber length and average fiber diameter of the fibrous reinforcement (B1) can be measured by observation with a scanning electron microscope (SEM), and the average aspect ratio (average fiber length / average fiber diameter) of the fibrous reinforcement (B1) can be calculated from the average fiber length and average fiber diameter. When measuring the average fiber length and average fiber diameter of the fibrous reinforcement (B1), for example, a plurality of fibrous reinforcements (B1) are photographed by a scanning electron microscope (SEM), 300 fibrous reinforcements (B1) are randomly selected from the observed images, and their fiber lengths and fiber diameters are measured. Then, the total fiber lengths are accumulated and divided by the number to be called the average fiber length, and the total fiber diameters are accumulated and divided by the number to be called the average fiber diameter.
[0056] Specific examples of plate-shaped reinforcing materials (B2) include mica, mica, sericite, illite, talc, kaolinite, montmorillonite, boehmite, smectite, vermiculite, potassium titaniumate, lithium potassium titaniumate, or magnesium potassium titaniumate. These plate-shaped reinforcing materials (B2) may be used as a single type or in combination of multiple types. In addition, in the present invention, the term "plate-shaped" includes, in addition to plate-shaped, flake-shaped, scale-shaped, etc.
[0057] The plate-shaped reinforcing material (B2) is preferably made of particles with a Mohs hardness of 2 or more and 5 or less, and more preferably mica, in order to suppress the generation of burrs during the drilling process and further improve the drilling precision.
[0058] In order to further enhance machinability when cutting or slicing a member for machining or when drilling a hole with a drill bit, the plate-shaped reinforcing member (B2) preferably has a maximum diameter (major axis) of 1 μm to 30 μm, and more preferably 1 μm to 10 μm. The minor axis of the plate-shaped reinforcing member (B2) preferably has a minor axis of 0.5 μm to 20 μm, and more preferably 0.5 μm to 10 μm. Furthermore, although they are referred to as the maximum diameter (major axis) and minor axis for convenience, a maximum diameter (major axis) and a minor axis of approximately the same length, i.e., a square or close to it, are also included in the plate shape. The thickness of the plate-shaped reinforcing member (B2) preferably has a thickness of 0.05 μm to 2 μm, and more preferably 0.05 μm to 1 μm. The aspect ratio (maximum diameter / thickness) of the plate-shaped reinforcing material (B2) is preferably 20 to 400, and more preferably 50 to 300.
[0059] The maximum diameter (major axis), minor axis, thickness, and aspect ratio of the plate-shaped reinforcing material (B2) can be calculated from the average of the maximum diameter (major axis), minor axis, and thickness of the plate-shaped reinforcing material (B2) by, for example, photographing a plurality of plate-shaped reinforcing materials (B2) using a scanning electron microscope (SEM). For example, 300 plate-shaped reinforcing materials (B2) can be randomly selected from the SEM images, and the average major axis obtained by accumulating all the maximum diameters (major axis) and dividing by the number can be called the maximum diameter (major axis) of the plate-shaped reinforcing material (B2), and the average minor axis obtained by accumulating all the minor axis and dividing by the number can be called the minor axis of the plate-shaped reinforcing material (B2).
[0060] In addition, if it is difficult to measure the maximum diameter of the plate-shaped reinforcing material (B2), the average particle size of the plate-shaped reinforcing material (B2) may be measured. The plate-shaped reinforcing material (B2) is preferably 0.01㎛ to 25㎛ in terms of further improving machinability when cutting or slicing a member for machining or when drilling a hole with a drill bit, and is more preferably 0.05㎛ to 20㎛ in terms of average particle size.
[0061] The average particle size of the plate-shaped reinforcing material (B2) can be measured by the laser diffraction and scattering method. Specifically, the average particle size of the plate-shaped reinforcing material (B2) is the particle size at the cumulative 50% based on volume in the particle size distribution measured by the laser diffraction and scattering method (cumulative 50% particle size based on volume), i.e., D 50 It is (median diameter). This volume-based cumulative 50% particle size (D 50 ) is the particle size at the point where the cumulative value reaches 50%, calculated by determining the particle size distribution based on volume and counting the number of particles starting from the smallest particle size on a cumulative curve with the total volume set to 100%.
[0062] In addition, for the reinforcing material (B), a treatment layer containing a surface treatment agent may be formed on the surface of the reinforcing material (B) for the purpose of further improving dispersibility in the resin composition and further improving adhesion with the thermoplastic resin (A).
[0063] As for the surface treatment agent, examples include silane coupling agents, titanium coupling agents, etc., although not particularly limited. Among these, it is preferable that it be a silane coupling agent, and more preferable that it be an amino-based silane coupling agent, an epoxy-based silane coupling agent, or an alkyl-based silane coupling agent. The above surface treatment agent may be used alone or in a mixture of two or more types.
[0064] Examples of amino-based silane coupling agents include N-2-(aminoethyl)-3-aminopropylmethyldimethoxysilane, N-2-(aminoethyl)-3-aminopropyltrimethoxysilane, 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, 3-ethoxysilyl-N-(1,3-dimethylbutylidene)propylamine, N-phenyl-3-aminopropyltrimethoxysilane, N-(vinylbenzyl)-2-aminoethyl-3-aminopropyltrimethoxysilane, etc.
[0065] Examples of epoxy-based silane coupling agents include 3-glycidyloxypropyl(dimethoxy)methylsilane, 3-glycidyloxypropyltrimethoxysilane, diethoxy(3-glycidyloxypropyl)methylsilane, triethoxy(3-glycidyloxypropyl)silane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, etc.
[0066] Examples of alkyl silane coupling agents include methyltrimethoxysilane, dimethyldimethoxysilane, trimethylmethoxysilane, methyltriethoxysilane, ethyltrimethoxysilane, n-propyltrimethoxysilane, isobutyltrimethoxysilane, isobutyltriethoxysilane, n-hexyltrimethoxysilane, n-hexyltriethoxysilane, cyclohexylmethyldimethoxysilane, n-octyltriethoxysilane, n-decyltrimethoxysilane, etc.
[0067] As a method for forming a treatment layer containing a surface treatment agent on the surface of a reinforcing material (B), a conventionally known surface treatment method may be used. As a method for forming a treatment layer containing a surface treatment agent, for example, a wet method may be used in which the surface treatment agent is dissolved in a solvent that promotes hydrolysis (e.g., water, alcohol, or a mixture of these solvents) to form a solution, and the solution is sprayed onto the reinforcing material (B).
[0068] When applying the surface treatment agent to the surface of the reinforcing material (B), the amount of the surface treatment agent is not particularly limited, but in the case of the wet method, for example, the solution of the surface treatment agent can be sprayed such that the amount of the surface treatment agent is 0.1 to 20 parts by mass per 100 parts by mass of the reinforcing material (B).
[0069] In the cutting member of the present invention, the particle shape of the reinforcing material (B) is not particularly limited. However, from the perspective of suppressing the generation of burrs during the drilling process of the cutting member and further improving the drilling precision, it is preferable that the reinforcing material (B) contains either a fibrous reinforcing material (B1) or a plate-shaped reinforcing material (B2), and it is more preferable that it contains either a fibrous reinforcing material (B1) with a Mohs hardness of 2 or more and a plate-shaped reinforcing material (B2) with a Mohs hardness of 2 or more and 5 or less. In this case, at least a portion of the surface of either the fibrous reinforcing material (B1) or the plate-shaped reinforcing material (B2) may be covered by a treatment layer formed by a surface treatment agent.
[0070] In the present invention, the content of the reinforcing material (B) is preferably 0.1 mass% to 60 mass% in the total amount of 100 mass% of the resin composition, more preferably 5 mass% to 60 mass%, even more preferably 5 mass% to 55 mass%, particularly preferably 5 mass% to 45 mass%, particularly more preferably 10 mass% to 40 mass%, most preferably 15 mass% to 40 mass%, and particularly most preferably 20 mass% to 35 mass%.
[0071] By setting the content of the reinforcing material (B) to the above range, the occurrence of burrs during the drilling process of a cutting member can be suppressed, and the drilling precision can be further improved.
[0072] (Other additives)
[0073] The resin composition used in the present invention may contain other additives, such as inorganic fillers (barium sulfate, etc.) excluding reinforcing material (B), coloring agents (titanium dioxide, carbon black, etc.), laser direct structuring additives, conductive fillers excluding reinforcing material (B), antistatic agents, antioxidants, heat stabilizers, ultraviolet absorbers, light stabilizers, weathering agents, light-resistant agents, release agents, lubricants, fluidity improvers, plasticizers, impact resistance improvers, flame retardants (phosphazene-based compounds, phosphate ester-based compounds, condensed phosphate ester-based compounds, etc.), anti-dripping agents, nucleation agents (fine talc, etc.), dispersants, vibration dampeners, neutralizing agents, and anti-blocking agents, to the extent that the desired physical properties are not impaired. One of these may be used alone, or two or more may be used in combination.
[0074] As for the coloring agent, there are no particular limitations as long as it can color the resin composition, but examples include inorganic pigments, organic pigments, dyes, etc. From the perspective of further improving the heat resistance of the workpiece for machining, it is preferable that the coloring agent be an inorganic pigment. Examples of inorganic pigments include carbon black, titanium dioxide, zinc oxide, Bengala, iron oxide-based pigments, ultramarine, cobalt blue, chromium oxide, titanium yellow, zinc-iron-based brown, spinel green, lead chromate-based pigments, cadmium-based pigments, copper-chromium-based black, copper-iron-based black, etc.
[0075] Examples of conductive fillers include carbons such as conductive carbon black and carbon fiber; inorganic fillers excluding reinforcing material (B) with the surface coated with a conductive material such as carbon or tin oxide / antimony oxide; powders or fibers such as iron, nickel, copper, silver, gold, and aluminum.
[0076] Examples of antistatic agents include anionic antistatic agents such as sodium alkylsulfonate, sodium alkylbenzenesulfonate, and alkyl phosphate; cationic antistatic agents such as alkylsulfonate phosphonium, alkylbenzenesulfonate phosphonium, and quaternary ammonium salt compounds; nonionic antistatic agents such as polyoxyethylene derivatives, polyhydric alcohol derivatives, and alkylethanolamine; low molecular weight antistatic agents such as polyoxyethylene derivatives, polyhydric alcohol derivatives, and alkylethanolamine; and high molecular weight antistatic agents such as polyethylene glycol methacrylate copolymer, polyetheramide, polyetheresteramide, polyetheramideimide, polyalkylene oxide copolymer, polyethylene oxide-epichlorhydrin copolymer, and polyether ester. Among these, it is preferable that the antistatic agent be a high molecular weight antistatic agent.
[0077] The amount of other additives is not particularly limited as long as it is within a range that does not impair the desirable physical properties of the cutting member of the present invention. The amount of other additives is typically 30 mass% or less, preferably 10 mass% or less, and more preferably 5 mass% or less, based on 100 mass% of the total resin composition.
[0078] Method for manufacturing a component for machining
[0079] (Method for manufacturing a resin composition)
[0080] In the method for manufacturing a cutting member according to the present invention, a resin composition is first prepared. The resin composition can be prepared by heating and mixing (particularly melt mixing) a mixture containing a thermoplastic resin (A) and a reinforcing material (B), and, if necessary, other additives. For melt mixing, a known melt mixing device, such as a twin-screw extruder, may be used.
[0081] The resin composition can be manufactured specifically by the following methods: (1) pre-mixing each component in a mixer (tumbler, Henschel mixer, etc.), melt-mixing in a melt-mixing device, and pelletizing with a pelletizing means (pelletizer, etc.); (2) adjusting a masterbatch of the desired component, mixing other components as needed, melt-mixing in a melt-mixing device, and pelletizing; (3) supplying each component to a melt-mixing device and pelletizing. The obtained pellets may be in a granular or particulate form by known methods.
[0082] The processing temperature in melt mixing is not particularly limited as long as it is a temperature at which the thermoplastic resin (A) can be melted. Typically, the cylinder temperature of the melt mixing apparatus used for melt mixing is set slightly higher than the melting point of the resin, and adjusted to a range where the resin composition can be melted at the actual cylinder temperature. In this way, the resin composition of the present invention that exhibits the desired effect is manufactured.
[0083] (Method of manufacturing and use of a component for machining)
[0084] With respect to the obtained resin composition, the cutting member of the present invention can be obtained by forming it using known resin molding methods such as injection molding, insert molding, compression molding (press molding), blow molding, inflation molding, and extrusion molding, depending on the type, use, shape, etc. of the intended cutting member (resin molded body). The molding method of the resin composition is preferably injection molding, compression molding, or extrusion molding from the perspective of forming a molded body having a plate-like portion as described below. From the perspective of further suppressing the generation of burrs, the molding method of the resin composition is more preferably compression molding or extrusion molding, and compression molding is even more preferable. From the perspective of further shortening the processing time, the molding method of the resin composition is preferably injection molding. In addition, in this case, the cutting parameters can be adjusted to a more suitable range, further suppressing the generation of burrs, or processing can be performed in a shorter time. Furthermore, in the molding method of the resin composition, a method combining the above-described molding methods may be adopted.
[0085] A cutting member obtained by molding a resin composition has excellent heat resistance, dimensional stability, and machinability during cutting or slicing, or during drilling with a drill bit, and in particular, can improve drilling precision while suppressing the generation of burrs during drilling.
[0086] In addition, the machining member obtained as described above satisfies the machinability parameters described above. Furthermore, the machinability parameters described above can be adjusted, for example, by changing the type or content of the thermoplastic resin (A) and reinforcing material (B) included in the resin composition constituting the machining member, or by changing the molding method or molding conditions during manufacturing.
[0087] In the present invention, it is preferable that the moisture content of the cutting workpiece obtained as described above is 0.01 mass% to 1.00 mass% before cutting or slicing. The moisture content is preferably 0.01 mass% or more, more preferably 0.05 mass% or more, preferably 1.00 mass% or less, more preferably 0.50 mass% or less, and even more preferably 0.25 mass% or less.
[0088] The cutting member of the present invention is preferably a molded body having a plate-like portion, from the perspective of performing multiple precision holes to accommodate the high precision accompanying the miniaturization of semiconductors or components. When the cutting member is a molded body having a plate-like portion, regarding the shape of the molded body having the plate-like portion, for example, it is preferable to have a plate-like portion (flat plate) with a thickness exceeding 1.0 mm in a part of the molded body, and it may also have a shape such as a round bar, pipe, or irregular part in addition to the plate-like portion (flat plate). From the perspective of the cutting performance of the cutting member, if the cutting member has a shape of a round bar other than the plate-like portion (flat plate), it is preferable that the diameter of the round bar-shaped portion exceeds 1.0 mm. Furthermore, if the cutting member has a shape of a pipe other than the plate-like portion (flat plate), it is preferable that the thickness of the pipe-shaped portion exceeds 1.0 mm. In addition, if the workpiece for machining has a shaped portion in addition to the plate portion, it is desirable that the thickness of the thickest part of the shaped portion exceeds 1.0 mm. Here, a shaped portion refers to a part having an arbitrary cross-sectional shape different from the cross-sectional shape of a plate, round bar, pipe, etc. If the shaped portion is composed of a thick portion, such as a concave or convex shape, and a thin portion, it is desirable from the perspective of the machinability of the workpiece for machining that the thickness of the thin portion exceeds 0.5 mm. In addition, the workpiece for machining may, of course, be composed only of a plate portion.
[0089] The cutting member of the present invention can be used to obtain various secondary molded products, such as resin parts, by performing cutting, cutting, or drilling (machining). Specific applications include, in the electrical and electronic field, wafer carriers, wafer cassettes, spin chucks, tote bins, wafer boats, IC chip trays, IC chip carriers, IC transport tubes, semiconductor test sockets (IC test sockets), burn-in sockets, pin grid array sockets, quad flat packages, leadless chip carriers, dual inline packages, small outline packages, reel packing, test jigs for chip components such as multilayer ceramic capacitors (MLCC), various cases, storage trays, transport device parts, or magnetic card readers.
[0090] The cutting member of the present invention can be suitably used in devices that use contact probe pins where the occurrence of burrs causes malfunction or where precision in drilling is required, and in particular, it can be suitably used as a member having a plate-like portion used in the manufacture of semiconductor inspection jigs.
[0091] Devices using such contact probe pins include, for example, semiconductor test jigs such as semiconductor test sockets (IC test sockets), test jigs for chip components such as multilayer ceramic capacitors (MLCC), printed circuit board test jigs, flexible printed circuit board test jigs, TAB (Tape Automated Bonding) tape test jigs, and probe cards for wafer test.
[0092] <Method of using the machining component>
[0093] The cutting member of the present invention can be used, for example, in a method for suppressing the generation of burrs during a hole-drilling process of a plate-shaped workpiece. In this method, when the cutting member of the present invention has the plate-shaped portion described above, the generation of burrs during the hole-drilling process can be suppressed by performing a hole-drilling process on this plate-shaped portion. Furthermore, the cutting member of the present invention can be used in a method for improving the precision of a hole-drilling process of a plate-shaped workpiece. In this method, when the cutting member of the present invention has the plate-shaped portion described above, the precision of a hole-drilling process can be improved by performing a hole-drilling process on this plate-shaped portion.
[0094] Examples
[0095] The present invention will be specifically described below based on examples and comparative examples, but the present invention is not limited thereto. Furthermore, the raw materials used in the examples and comparative examples are specifically as follows.
[0096] <Ingredients>
[0097] (Amorphous thermoplastic resin)
[0098] Polyetherimide (PEI) Resin 1: Melt viscosity 720 Pa·s (380°C, shear rate 122 sec) -1 ), glass transition temperature 217℃, manufactured by SABIC, product name "Ultem1010-1000"
[0099] Polyetherimide (PEI) Resin 2: Melt viscosity 1120 Pa·s (380°C, shear rate 122 sec) -1 ), glass transition temperature 217℃, manufactured by SABIC, product name "Ultem1000-1000"
[0100] Polyetherimide (PEI) Resin 3: Melt viscosity 340 Pa·s (380°C, shear rate 122 sec) -1 ), glass transition temperature 217℃, manufactured by SABIC, product name "Ultem1040A-1000"
[0101] Polyethersulfone (PES) resin: Melt viscosity 220 Pa·s (380°C, shear rate 122 sec) -1 ), glass transition temperature 225℃, manufactured by BASF, product name "Ultrason E0510"
[0102] (Weapon reinforcement)
[0103] Potassium titanium dioxide fiber: Fibrous potassium hexatitanate, average fiber length 15㎛, average fiber diameter 0.5㎛, Mohs hardness: 4 (Manufactured by Otsuka Chemical, product name "Tismo N102")
[0104] Wollastonite fiber: Average fiber length 25㎛, average fiber diameter 3.5㎛, aspect ratio 7.1, Mohs hardness: 4.5 (Manufactured by Otsuka Kagaku Co., Ltd., product name "Vistal K101")
[0105] Titania fiber: Monoclinic titania fiber coated with a conductive material containing tin oxide / antimony oxide on its surface, average fiber length 12 µm, average fiber diameter 0.4 µm, Mohs hardness: 5
[0106] Glass fiber: Average fiber length 3 mm, average fiber diameter 16 µm, Mohs hardness: 6 (Made by Nippon Denki Glass Co., Ltd., Product name "ECS03 T-717")
[0107] Mica: Major axis (maximum diameter) 6.0 µm, thickness 0.1 µm, aspect ratio 60, Mohs hardness: 2.8
[0108] (Other additives)
[0109] Coloring agent: Mixture of carbon black (50 mass%) and low molecular weight polyethylene (50 mass%), manufactured by Ota Kasei Co., Ltd., trade name "EB-15 Grain Black"
[0110] Additives: Heat stabilizer, manufactured by Sumitomo Chemical, product name "Sumiriser GA-80"
[0111] (Measurement of melt viscosity)
[0112] The melt viscosity of polyetherimide (PEI) resin was measured using a melt viscosity measuring device (manufactured by Toyo Seiki Seisakushosha, product name "Capilograph 1D"), with a shear rate of 122 sec at a temperature (380°C) 163°C higher than the glass transition temperature of the polyetherimide (PEI) resin. -1 Under the conditions, measurements were taken using a 1.0 mm φ × 10 mm capillary rheometer.
[0113] The melt viscosity of polyethersulfone (PES) resin was measured using a melt viscosity measuring device (manufactured by Toyo Seiki Seisakusho Co., Ltd., product name "Capilograph 1D"), with a shear rate of 122 sec at a temperature (380°C) 155°C higher than the glass transition temperature of the polyethersulfone (PES) resin. -1 Under the conditions, measurements were taken using a 1.0 mm φ × 10 mm capillary rheometer.
[0114] (Measurement of glass transition temperature)
[0115] The glass transition temperature of polyetherimide (PEI) resin and polyethersulfone (PES) resin was measured in accordance with JIS-K7121 using a differential calorimetry device (manufactured by Hitachi High-Tech Science, product name “DSC7000X”), 10 mg of the sample was placed in a measuring aluminum cell, and under a nitrogen air flow of 100 ml / min, the temperature was raised from room temperature to 50°C at a heating rate of 10°C / min, maintained at 50°C for 5 minutes, and then raised to 400°C at a heating rate of 10°C / min.
[0116] (Average fiber length, average fiber diameter, and aspect ratio)
[0117] The average fiber length, average fiber diameter, and aspect ratio of potassium titanium dioxide fibers or wollastonite fibers were obtained from 300 random average values measured by scanning electron microscope (SEM) observation.
[0118] <Preparation of Resin Composition and Evaluation Samples>
[0119] (Examples 1 to 10 and Comparative Examples 1 and 2)
[0120] The resin compositions were melt-kneaded using a twin-screw extruder at the mixing ratios shown in Tables 1 and 2 to produce pellets (resin compositions), respectively. In addition, the cylinder temperature of the twin-screw extruder was 100°C to 160°C higher than the glass transition temperature of the thermoplastic resin.
[0121] Molding was performed using the obtained pellets, and they were formed into JIS test specimens and business card-shaped plates (test specimens) to measure mechanical properties, load bending temperature, fracture toughness, cutting resistance, and cutting time, and used as evaluation samples (resin molded bodies) for machining components. In addition, regarding the molding method of the pellets, injection molding was used in Examples 1 to 4, 5, and 9 and Comparative Examples 1 and 2. Compression molding (press molding) was used in Examples 6, 8, and 10. Extrusion molding was used in Example 7. Meanwhile, in injection molding, the cylinder temperature of the molding machine was at least 100°C higher than the glass transition temperature of the thermoplastic resin, and the mold temperature was about 30°C higher than the glass transition temperature of the thermoplastic resin. In press molding, the mold temperature of the molding machine was at least 90°C higher than the glass transition temperature of the thermoplastic resin, and melt pressing was performed for 2 minutes with a load of 5t applied after maintaining the heat for a certain period of time. The ejection temperature after cooling was around 50°C. In addition, in extrusion molding, the cylinder temperature was about 100°C higher than the glass transition temperature of the thermoplastic resin, and the mold temperature was about 60°C higher than the glass transition temperature of the thermoplastic resin. In addition, for the evaluation samples of the compression molded (press molded) body and the extrusion molded body, test specimens were cut from sheet metal using a bench circular saw. The dimensions of the evaluation samples were adjusted to match the injection molded body. Furthermore, the evaluation samples of the compression molded body and the extrusion molded body produced in this manner will also be collectively referred to as JIS test specimens.
[0122] <Evaluation>
[0123] The following evaluations were performed on the evaluation samples (test specimens) or resin compositions prepared in Examples 1 to 10 and Comparative Examples 1 and 2. The results are shown in Tables 1 and 2 below.
[0124] (Bending strength, bending modulus)
[0125] In accordance with JIS K7171, bending strength and bending modulus were measured for a JIS test specimen (length: 10.1 mm, width: 110 mm, thickness: 4.1 mm) by a 3-point bending test with a spacing of 60 mm using an Autograph AG-5000 (manufactured by Shimadzu Seisakushosha).
[0126] (Notch-attached IZOD impact value)
[0127] In accordance with JIS K7110, the impact value of a notched IZOD was measured on a JIS test specimen (length 13 mm, width 63 mm, thickness 4 mm).
[0128] (Melting viscosity)
[0129] The melt viscosity of the resin compositions of Examples 1 to 10 and Comparative Examples 1 and 2 was measured using a melt viscosity measuring device (manufactured by Toyo Seiki Seisakusho, trade name "Capilograph 1D") at a shear rate of 122 sec -1 and measured under conditions of a temperature of 380℃.
[0130] (Load bending temperature)
[0131] In accordance with the JIS K7191A method, an edge-wise test was performed using an HDT measuring device (manufactured by Toyo Seiki Seisakushosha, product name "HDT. VSPT. TESTER S-3M") to measure the load-bending temperature (°C). The test conditions were as follows: the load-bending temperature was measured using a bending test specimen (length: 10.1 mm, width: 110 mm, thickness: 4.1 mm) as a JIS test specimen. The load-bending temperature (°C) for each test specimen was determined in accordance with the JIS K7191A method. The starting temperature was set to 50°C, the heating rate to 120°C / h, the load to 1.8 MPa, and the distance between supports to 100 mm.
[0132] (Destructive Toughness K1c)
[0133] For the JIS test specimens (length 13 mm, width 63 mm, thickness 4 mm) of the examples and comparative examples, fracture toughness K1c was measured using a fracture toughness measuring device (manufactured by Shimadzu Seisakusho, trade name “Mechanical Testing Machine Autograph AGS-J”) in accordance with ASTM D5045-93. Fracture toughness K1c represents crack propagation resistance, and a higher value indicates higher fracture toughness.
[0134] (Cutability parameter)
[0135] The machinability parameter defined by the following Equation (1) was obtained from the fracture toughness K1c and bending modulus of the evaluation sample.
[0136]
[0137] (Cutting resistance and cutting time)
[0138] For the business card-shaped plates (length 50 mm, width 90 mm, thickness 3 mm) of the examples and comparative examples, a square with a side length of 30 mm was cut to produce a flat plate for evaluating machinability.
[0139] In addition, a drill fixing jig was manufactured to hold a drill (manufactured by Saito Seisakushosha, product number "ADR-1.0") used for cutting evaluation. In addition, the shape of the manufactured drill fixing jig is as shown in FIG. 1.
[0140] The above-mentioned flat plate and drill fixing jig for evaluating machinability were installed in a friction wear tester (manufactured by A&D, model “EFM-3-H”), and a cutting evaluation was initiated with a load of 1100g and a rotational speed of 0.3m / s. The cutting resistance value and cutting time were measured from the time the drill entered the flat plate until it penetrated. At this time, the flat plate for evaluating machinability was installed on the rotating side and the drill fixing jig was installed on the fixed side.
[0141] In addition, regarding the fact that the hole was not penetrated even after more than 1 minute had passed since the cutting evaluation began, it was stated in the cutting time column of Table 1 that "the hole was not penetrated" and that it was not a desirable evaluation regarding machinability.
[0142] (Burr generation amount)
[0143] After measuring the cutting resistance and cutting time, the above-mentioned plate for evaluating machinability was examined using an optical microscope (Keyence, product number "One Shot 3D Measurement Macroscope VR-3000"), with the magnification of the optical microscope set to 150x, and visual observation was performed on the maximum length (longer side) of the burrs occurring around the hole after drilling and the number of burrs to evaluate the precision of the hole after drilling.
[0144] As criteria for evaluating the precision of the hole drilling after the hole drilling process, A was defined as no burrs observed (number of burrs: 0), B as the maximum length (longer side) of the observed burrs being 50 μm or less and the number of burrs being 1, and C as the maximum length (longer side) of the observed burrs being more than 50 μm and the number of burrs being 2 or more. The results are shown in Tables 1 and 2.
[0145]
[0146]
[0147] As is evident from Tables 1 and 2, in the machining members of Examples 1 to 10, the Mohs hardness of the inorganic reinforcing material is 5 or less, and the machinability parameter is 15m 1 / 2 to 100m 1 / 2 It was confirmed that, within the range, the cutting resistance is low, the cutting time can be shortened, and the machinability is excellent, and the generation of burrs can be suppressed.
[0148] Meanwhile, in the machining members of Comparative Examples 1 and 2, the machinability parameter is 100m 1 / 2 Since the Mohs hardness of the weapon reinforcement is greater than 5, there were no cases where the hole was penetrated under the above cutting conditions.
[0149] As such, the cutting member of the present invention has excellent cutting performance and can suppress the generation of burrs during cutting, so it can be used in devices using contact probe pins where the generation of burrs causes malfunction and precision of hole drilling is required, and in particular, it can be used in semiconductor inspection jigs.
Claims
Claim 1 A machining member comprising a molded body of a resin composition containing a thermoplastic resin (A) and a reinforcing material (B), wherein the machining member is a molded body having a plate-like portion, the thermoplastic resin (A) is an amorphous thermoplastic resin, the reinforcing material (B) is an inorganic reinforcing material having a Mohs hardness of 5 or less, and the machinability parameter defined by the following equation (1) from the fracture toughness K1c and bending modulus of the machining member is 15m 1 / 2 to 100m 1 / 2 A member for cutting, characterized by being. Claim 2 A machining member according to claim 1, wherein the load bending temperature (HDT) of the machining member at a load of 1.8 MPa is 150°C or higher. Claim 3 A member for cutting, wherein, in claim 1 or 2, the thermoplastic resin (A) is at least one selected from the group consisting of polyetherimide resin, polyethersulfone resin, and polyamideimide resin. Claim 4 A member for machining according to claim 1 or 2, wherein the aspect ratio of the reinforcing material (B) is 3 to 100. Claim 5 A member for cutting, wherein, in claim 1 or 2, the reinforcing material (B) is a fibrous reinforcing material having an average fiber length of 1 μm to 300 μm. Claim 6 A member for machining according to claim 1 or 2, wherein the reinforcing material (B) is at least one fiber selected from the group consisting of potassium titaniumate fiber, wollastonite fiber and titania fiber. Claim 7 A member for machining according to claim 1 or 2, wherein, in 100 mass% of the total amount of the resin composition, the content of the thermoplastic resin (A) is 20 mass% to 95 mass% and the content of the reinforcing material (B) is 5 mass% to 55 mass%. Claim 8 In claim 1 or 2, the thermoplastic resin (A) is a polyetherimide resin, and the shear rate of the resin composition is 122 sec -1 and a member for machining having a melt viscosity of 300 Pa·s to 2600 Pa·s at a temperature of 380°C. Claim 9 In claim 1 or 2, the thermoplastic resin (A) is a polyethersulfone resin, and the shear rate of the resin composition is 122 sec -1 and a member for machining, having a melt viscosity of 230 Pa·s to 550 Pa·s at a temperature of 380°C. Claim 10 A member for machining, wherein, in claim 1 or 2, the compression molded body or extrusion molded body of the resin composition containing the thermoplastic resin (A) and the reinforcing material (B). Claim 11 A member for machining, wherein, in claim 1 or 2, the injection-molded body of the resin composition containing the thermoplastic resin (A) and the reinforcing material (B). Claim 12 delete Claim 13 A cutting member used in at least one selected from the group consisting of a semiconductor inspection socket, a wafer inspection probe card, a printed circuit board inspection jig, a TAB (Tape Automated Bonding) tape inspection jig, a flexible printed circuit board inspection jig, and an inspection jig for chip components, according to claim 1 or 2. Claim 14 A method for manufacturing a cutting member as described in claim 1 or 2, comprising a process of obtaining a cutting member having a plate-like portion by molding a resin composition containing the thermoplastic resin (A) and the reinforcing material (B). Claim 15 A method of using a cutting member, wherein the plate portion of the cutting member obtained by molding the resin composition is drilled, in the method of manufacturing a cutting member described in paragraph 14.